Eyes without a face [videorecording (DVD)] - Franju, Georges, 1912-1987; Brasseur, Pierre, 1905-1972; Valli, Alida, 1921-2006; Scob, Édith (Criterion collection, 2004)
A plastic surgeon, holed up in a Paris mansion, is obsessively slicing off the faces of kidnapped women and grafting the flayed skin onto the rotting countenance of his beloved young daughter, disfigured in an automobile accident.